2010
DOI: 10.1002/pbc.22821
|View full text |Cite
|
Sign up to set email alerts
|

A phase I study of zoledronic acid and low‐dose cyclophosphamide in recurrent/refractory neuroblastoma: A new approaches to neuroblastoma therapy (NANT) study

Abstract: Background Zoledronic acid, a bisphosphonate, delays progression of bone metastases in adult malignancies. Bone is a common metastatic site of advanced neuroblastoma. We previously reported efficacy of zoledronic acid in a murine model of neuroblastoma bone invasion prompting this Phase I trial of zoledronic acid with cyclophosphamide in children with neuroblastoma and bone metastases. The primary objective was to determine recommended dosing of zoledronic acid for future trials. Procedure Escalating doses o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 46 publications
2
44
1
Order By: Relevance
“…The data (Figure 6B) demonstrated an increase in pSTAT3 activation in the presence of 10 ng/mL of sIL-6R and above but not at lower concentrations (0.1 and 1.0 ng/mL). These sIL-6R concentrations are found the blood of cancer patients (35). Because neuroblastoma cells do not produce sIL-6R and are thus dependent of a paracrine source (16), we examined whether it was produced by normal cells in the tumor microenvironment.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…The data (Figure 6B) demonstrated an increase in pSTAT3 activation in the presence of 10 ng/mL of sIL-6R and above but not at lower concentrations (0.1 and 1.0 ng/mL). These sIL-6R concentrations are found the blood of cancer patients (35). Because neuroblastoma cells do not produce sIL-6R and are thus dependent of a paracrine source (16), we examined whether it was produced by normal cells in the tumor microenvironment.…”
Section: Resultsmentioning
confidence: 91%
“…To test this hypothesis, we examined whether the addition of sIL-6R at a concentration of 25 ng/mL, which is within the range of the levels detected in the blood of patients with neuroblastoma (10–90 ng/mL; Ref. 34, 35), would result in STAT3 activation in the presence of concentrations of IL-6 in the (0.1 to 10) ng/mL range. These experiments demonstrated that when IL-6 was used alone, a concentration of 10 ng/mL was necessary to activate STAT3 whereas when used in combination with sIL-6R (25 ng/mL), a concentration of 0.1 ng/mL of IL-6 was sufficient for STAT3 activation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Targeting osteoclasts with bisphosphonates like zoledronic acid has been tested in patients with bone metastasis and the results of a Phase I trial completed by the New Advances in Neuroblastoma Therapy (NANT) consortium demonstrated the safety and efficacy of zoledronic acid [142]. This agent is now tested with cyclophosphamide in a Phase I clinical trial by Baylor College of Medicine (NCT00206388) and in combination with Interleukin-2 in refractory neuroblastoma by University of Alabama at Birmingham (NCT01404702).…”
Section: Therapeutic Considerationmentioning
confidence: 99%
“…[18] A similar approach has been assessed in a recent New Advances to Neuroblastoma Therapy trial of ZOL in combination with oral cyclophosphamide in refractory NB patients, although this trial did not study γδ T cell expansion. [19] …”
Section: Discussionmentioning
confidence: 99%